TINJAUAN PENGORGANISASIAN FUNGSI PADA DOMPET PRIA - Dena Anggita (Universitas Mercu Buana, 2019)
This study aims to determine the types of men's wallets along with items and what features are contained in the wallet. A wallet is a container that is used to store money or valuable cards. Along with the times and lifestyles, wallets come with various designs and features, but many wallets have changed because of the needs and development of payment technology, so users must be able to adjust wallet designs according to their needs. This study uses a qualitative method, the research method used to examine natural object conditions where the researcher is a key instrument, source and data sampling is done in a